ANALISIS PENGARUH ORIENTASI PASAR TERHADAP KINERJA PEMASARAN PADA PERUSAHAAN PENGOLAHAN DI KOTA SEMARANG - Daniel Manek (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2018)
Purpose of this study was to examine and measure the market orientation effects on marketing performance. The population used in this study is the manufacturing companies in Semarang, consist of furniture, food & beverages, printing/offset, machinery & workshop, garment & footwear, metal industry, plastic waste cycle, soap& cleansing ware and plywood. Number of respondent in this research is 105 unit of companies, each company represented by their owner or manager. The results showed that market orientation is positively and significantly affect the marketing performance. Moreover, the model developed in this study proved that: 1) Market orientation result also positively influence marketing performance through process of product adaptation and business strategy quality; 2) Business strategy and product adaptation has positive effect on competitive advantage; 3) Product adaptation and competitive advantage has positive influence to marketing performance.